Influence of Bolt Tightening's Force to the Strength of Connection System of Bamboo Truss Structure with Wooden Clamp. (2017) - Masdar, Astuti; Suhendro, Bambang; Siswosukarto, Suprapto; Sulistyo, Djoko
Abstract: Bamboo is an environmentally friendly construction material that has great potential to be used as sustainable material construction for future generation. Bamboo can be used in a wide range of structure components such as beams, columns, floors, frame and truss. As a truss structure, the connection system determines the strength of bamboo truss structures. The bolt tightening force on the truss structure greatly affects the strength of bamboo truss structure. In this study, there are three variations of bolt tightening force on connection system of bamboo truss structure with wooden clamp. In this study, a preliminary research on varying bolt tightening forces on the connection system used with a variety of tightening force by torsion meter, respectively, i.e. 0.5 kgf, 0.8 kgf and 1 kgf unit torsi meter or equal to 1770 N, 2830 N and 3540 N. The results that bolt tightening force amounting of 2830 N, produced the optimum connection strength on bamboo truss structure with wooden clamps.